2019
DOI: 10.4103/jpbs.jpbs_293_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dental health education on the knowledge and attitude among expectant mothers: A questionnaire study

Abstract: Background: Although dental caries levels have declined and stabilized the world over, the problem of early childhood caries has remained persistent in many areas of the world affecting certain segments of society, especially the socially deprived, who remain at high risk to this disease. Parents have an essential role in mediating between their children and environment for which prenatal period is the best time for health interventions. This mediation is done through preventive services they prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous research indicated an increase or improvement in action planning for OH as key to achieving optimal behavior in the field of OH [59]. Experts believe that attitudes are obtained based on the individual experience of behavior or alternative experiences through learning from others; hence, as behavior is directly experienced, positive beliefs are strengthened in relation to the behavior outcome, and then act as incentives for its continuation [60]. Our findings were not unexpected and indicate that the educational intervention improved subjective norms in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated an increase or improvement in action planning for OH as key to achieving optimal behavior in the field of OH [59]. Experts believe that attitudes are obtained based on the individual experience of behavior or alternative experiences through learning from others; hence, as behavior is directly experienced, positive beliefs are strengthened in relation to the behavior outcome, and then act as incentives for its continuation [60]. Our findings were not unexpected and indicate that the educational intervention improved subjective norms in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…The results of various studies in Iran also indicate the effectiveness of education on the awareness of pregnant women in this area and the promotion of oral care behaviours. 30 31 …”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women supported the inclusion of oral health education and preventive measures during pregnancy, as well as the inclusion of oral examinations on the prenatal checklist and the establishment of a referral system as strategies for integrated prenatal oral health care [27]. Selvarajan et al [28] demonstrated that dental health education significantly improves both the knowledge and attitude of expectant mothers.…”
Section: Discussionmentioning
confidence: 99%